Comparative evaluation of the efficacy and safety of ormeloxifene and norethisterone in abnormal uterine bleeding - Fatima, Ayesha; Siddiqua, Syeda Ayesha (International Journal of Research in Medical Sciences, 2024)
Background: Abnormal uterine bleeding is a typical condition for women of reproductive age. It can be painful and uncomfortable, create social disgrace, and have a considerable impact on health-related quality of life. Several studies have shown that ormeloxifene and norethisterone are useful in the treatment of abnormal uterine bleeding, however there is a scarcity of data comparing the efficacy and safety of these medicines. Methods: A prospective comparative study was conducted over 100 women, age group of 30-50 years, attending the gynecology outpatient department with subjective complaints of heavy menstrual bleeding at a tertiary care hospital, in Hyderabad. Group A (n=50) received 60 mg of ormeloxifene and Group B (n=50) received 5mg of norethisterone, respectively. Ethical approval was taken from the institutional ethical committee. Results: 38% aged 41-45, 86% had irregular cycles, 76% reported subjective improvement in group A, and 38% in group B. Group A showed a mean difference of 80.22 in decreasing PBAC score, 0.70 in hemoglobin rise, and 3.5 in decreasing ET, while group B showed 53.70 in PBAC decrease, 0.28 in hemoglobin rise, and 1.76 in endometrial thickness reduction. Both groups have no notable side effects and no significant p value. Conclusions: Reducing PBAC score, subjective improvement, hemoglobin, and endometrial thickness with ormeloxifene and norethisterone works. Ormeloxifene has a far greater effect than norethisterone and has fewer adverse effects.